The grammaticalisation of a copula in vernacular Arabic. Issue 1 (18th December 2019) - Camilleri, Maris; Sadler, Louisa
Abstract : It is standardly assumed that Arabic copula constructions with present tense interpretation involve either a null copula or a pronominal copula. This paper provides evidence that some Arabic vernaculars are developing a three-way split, with an additional copula form occurring in some predicational copula clauses. This form has grammaticalised out of the active participle form of the posture verb meaning 'sit'. While at different stages of development in different varieties of Arabic, this emergent copula shows the characteristics of a locative (temporary and/or permanent, depending on the variety) or contingent state (stage-level) copula, standing in contrast with the use of a null copula strategy, which marks characterising/defining individual-level properties. We propose a grammaticalisation trajectory for this copula in the Arabic varieties based on the comparative patterns of variation across those dialects, showing that the trajectory postulated for other, typologically distinct languages is also applicable to Arabic and hence providing further support for it. We suggest that there is also evidence of a distinct but related trajectory in some varieties which have developed a semantically bleached lexical existential predicate from this same form. We provide further evidence of the importance of the temporary/permanent split in the copula systems of Arabic arguing that the developing split copula system based on the active participle of the 'sit' verb is in alignment with the development of two other parallel split copula systems in other geographically diverse Arabic varieties, which use different bases/strategies for grammaticalisation.